Non-Fungible Token Sebagai Objek Jaminan Fidusia Guna Mengoptimalisasi Hak Kekayaan Intelektual - Iqbal Iqbal; Noor Saptanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research examines the problem of technological advances creating digital transformation in various aspects of life, one of which is art. Digital evolution in art, giving rise to various new creative expressions, one of which is Non-Fungible Tokens. NFT as a form of creative output has Copyright which is part of Intellectual Property Rights. Based on Government Regulation Number 24 of 2022 concerning Implementing Regulations for Law Number 24 of 2019 concerning the Creative Economy, Intellectual Property Rights can be used as a basis for financing the creative economy sector. This research aims as an effort to encourage the progress of the creative economy sector by examining NFTs as objects of Fiduciary Guarantees in order to optimize Intellectual Property Rights as the basis for financing schemes for the creative economy sector. This research is a prescriptive normative legal research. Types of secondary data include primary and secondary legal materials. The technique of collecting legal materials is done by literature study, then a conceptual approach is used. The results of this study indicate that NFTs have the potential to be used as objects of fiduciary guarantees, however, there are obstacles in regulations and mechanisms that have not been protected by the government, so it is necessary to adjust more specific regulations related to the use of digital assets in fiduciary schemes and education and increased digital literacy for financial institutions and creative economy actors regarding the potential and risks of using NFTs as objects of fiduciary guarantees.